Insights about serum sodium behavior after 24 hours of continuous renal replacement therapy - Romano, Thiago Gomes (Rev Bras Ter Intensiva, 2016)
OBJECTIVE: The aim of this study was to investigate the clinical and laboratorial factors associated with serum sodium variation during continuous renal replacement therapy and to assess whether the perfect admixture formula could predict 24-hour sodium variation. METHODS: Thirty-six continuous renal replacement therapy sessions of 33 patients, in which the affluent prescription was unchanged during the first 24 hours, were retrieved from a prospective collected database and then analyzed. A mixed linear model was performed to investigate the factors associated with large serum sodium variations (≥ 8mEq/L), and a Bland-Altman plot was generated to assess the agreement between the predicted and observed variations. RESULTS: In continuous renal replacement therapy 24-hour sessions, SAPS 3 (p = 0.022) and baseline hypernatremia (p = 0.023) were statistically significant predictors of serum sodium variations ≥ 8mEq/L in univariate analysis, but only hypernatremia demonstrated an independent association (β = 0.429, p < 0.001). The perfect admixture formula for sodium prediction at 24 hours demonstrated poor agreement with the observed values. CONCLUSIONS: Hypernatremia at the time of continuous renal replacement therapy initiation is an important factor associated with clinically significant serum sodium variation. The use of 4% citrate or acid citrate dextrose - formula A 2.2% as anticoagulants was not associated with higher serum sodium variations. A mathematical prediction for the serum sodium concentration after 24 hours was not feasible.